Kurikulum Pendidikan Ibnu Sina tentang Perkembangan Dasar Anak: Sebuah Studi Relevansi Kontemporer - Rusmini; Rohmadi, Yusup; Bakri, Syamsul (Universitas Veteran Bangun Nusantara, 2025)
ABSTRACT This study investigates the enduring relevance curriculum of Ibn Sina's (Avicenna's) 11th-century concepts of child education in contemporary pedagogical practice. Background: As modern education systems grapple with balancing cognitive and character development, Ibn Sina's holistic approach from the Islamic Golden Age offers valuable insights that remain understudied in current literature. Aims: The research examines three key objectives: (1) analyzing Ibn Sina's educational framework for children, (2) evaluating its alignment with modern developmental theories, and (3) identifying implementation strategies for Indonesian classrooms. Methods: A qualitative systematic review was conducted, analyzing primary sources (Ibn Sina's original texts) and 35 secondary sources (2018-2023 peer-reviewed articles) through thematic coding. Results: Findings reveal four persistent relevancies: (a) developmental stage-based curriculum mirroring modern constructivist approaches, (b) integrated moral-intellectual-physical development anticipating heutagogy principles, (c) non-punitive teaching methods aligning with trauma-informed education, and (d) teacher competency standards resembling Indonesia's Guru Penggerak framework. Conclusion: Ibn Sina's philosophy provides a viable model for addressing contemporary education gaps, particularly in character education and differentiated learning. Contributions: The study offers three practical innovations: (1) a crosswalk matrix connecting classical Islamic pedagogy with 21st-century skills, (2) evidence-based recommendations for Indonesia's Merdeka Curriculum reform, and (3) a theoretical framework for culturally responsive pedagogy in Muslim-majority contexts. Keywords: Islamic pedagogy, child development, curriculum design, educational philosophy